Changes in physical activity and sedentary behaviour following pulmonary rehabilitation in patients with COPD. (May 2017) - Mesquita, Rafael; Meijer, Kenneth; Pitta, Fabio; Azcuna, Helena; Goërtz, Yvonne M.J.; Essers, Johannes M.N.; Wouters, Emiel F.M.; Spruit, Martijn A.
Abstract: A more profound investigation about the responses in activity levels following pulmonary rehabilitation (PR) in patients with COPD is needed. We aimed to describe groups of patients with COPD according to patterns of change in physical activity and sedentary behaviour following PR. 90 patients with COPD (60% male; mean age 67 ± 8; median FEV1 47 (32–62) %pred) completed a comprehensive PR programme. A triaxial accelerometer was used to assess the time in sedentary behaviour, light activities and moderate-to-vigorous physical activity (MVPA). Additionally, exercise capacity, quality of life, and symptoms of anxiety and depression were assessed before and after PR. Six groups with different patterns of change in physical activity and sedentary behaviour were identified. The two most prevalent patterns were represented by good responders (increase in physical activity and reduction in sedentary behaviour, 34%) and poor responders (decrease in physical activity and increase in sedentary behaviour, 30%). Good responders had greater improvements in six-minute walk distance (6MWD) and symptoms of depression than poor responders ( P < 0.05 for all). Strong correlation was found between changes in sedentary behaviour and changes in light activities ( r s = −0.89; P < 0.0001). Changes in 6MWD correlated fairly with changes in sedentary behaviour ( r s = −0.26), light activities ( r s = 0.25), and MVPA ( r s = 0.24); P < 0.05 for all. Different patterns of change in activity levels following PR can be found in patients with COPD. Focusing on light physical activities might be a potential strategy to make patients less sedentary, but for this to be achieved prior (or at least parallel) improvements in functional capacity seem to be necessary. Highlights: Changes in activity levels after pulmonary rehabilitation are heterogeneous in COPD. Six groups of COPD patients with different patterns of change were identified. Good responders had the greatest improvements in exercise capacity and mood. Focusing on light physical activities might be important to make patients less sedentary. Improving functional capacity seems to be necessary for improving activity levels.